An NIR‐III 3P Excitable AIE Nanoprobe for High‐Quality Intravital Deep‐Brain Angiography - Zhijun Zhang; Hui Cheng; Zengming Yang; Xiangquan Deng; Miaomiao Kang; Ping Qiu; Ke Wang; Dong Wang; Ben Zhong Tang (Aggregate)
ABSTRACT Three‐photon (3P) fluorescence imaging (FLI) utilizing excitation wavelengths within the near‐infrared‐III (NIR‐III, 1600–1870 nm) window has emerged as a transformative modality for intravital imaging, owing to its combined advantages of excellent spatiotemporal resolution and remarkable tissue penetration. High‐performance fluorescent probes are the cornerstone of high‐quality NIR‐III 3P FLI. However, the construction of such probes is often hindered by inherent trade‐offs in molecular design principles, posing significant challenges for their performance optimization and practical application. Here, we propose a straightforward and effective strategy based on π‐bridge manipulation to reconcile those competing molecular design parameters and substantially enhance 3P fluorescence properties. Leveraging this approach, a robust AIE‐active small molecule, named TSSID, was developed, which exhibits bright NIR‐I (700–950 nm) emission under 1665 nm NIR‐III 3P excitation when formulated into nanoparticles (NPs). Remarkably, upon retro‐orbital injection into mice following craniotomy, TSSID NPs achieved the best performance in deep‐brain angiography among all reported organic 3P materials in terms of vascular imaging depth, signal‐to‐background ratio, spatial resolution, and hemodynamic imaging depth. Additionally, TSSID NPs demonstrated outstanding biocompatibility through systematic biosafety evaluations. This study provides an excellent imaging agent and useful molecular design philosophy, facilitating the development of advanced organic 3P FLI probes.